Analysis of Science Process Skills and Scientific Attitudes of Students in STEM Integrated Project-Based Learning - Fajrul Wahdi Ginting; Isna Rezkia Lukman; Mellyzar; Risma Andriani; Sapina Tiarani (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
In order to adapt to the rapid development of technology and information in the 21st century, various abilities and skills are required.As an instrument of social change and scientific attitudes, education has a responsibility to facilitate every learning process so that it is oriented to the needs of the times.This study uses a quantitative descriptive method that aims to analyze the results of Science Process Skills and Scientific Attitudes of students through the application of STEM (Science, Technology, Engineering and Math) integrated Project-Based Learning.The subjects in this study were 70 students who took Basic Physics lectures using a sampling technique, namely total sampling.The content validity of the instrument through analysis of the Vaiken index obtained an average index of 0.84 in the High category for the Science Process Skills instrument and an average index of 0.83 in the High category for the Scientific Attitude instrument, indicating that the instrument was declared valid and feasible.used.The results of the Science Process Skills assessment of students obtained the highest average in the Conducting Experiment aspect with a score of 89.29 and in the Very High criteria, while for the average of all aspects of Science Process Skills a score of 83.72 was obtained in the High criteria.For the results of the Scientific Attitude assessment, students obtained the highest average in the Curious Attitude aspect with a score of 94.29 and in the Very High criteria, while for the average of all aspects of Scientific Attitude, a score of 89.71 was obtained in the Very High criteria.Based on these results it can be stated that the implementation of PjBL – STEM has a positive impact and contribution to Science Process Skills and Scientific Attitudes of Students.